2018
DOI: 10.1111/apa.14567
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial showed that neonates received better pain relief from a higher dose of sucrose during venepuncture

Abstract: We showed that neonates received better pain relief from 0.5 mL than 0.2 mL sucrose during venepuncture but not after the needle was removed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…1 Newborns commonly experience pain due to a variety of reasons. 2,3 For example, in the first 3e4 days of life, they are subjected to routine invasive procedures such as vitamin K1 injections, 4 checking the anus for patency, 5 hepatitis B vaccination, 6 tuberculosis vaccination, 7 and neonatal screening tests. 8,9 Scientific evidence demonstrates that although newborns lack the ability to express their discomfort and stress in words, they tend to experience the pain at a higher intensity than older children and adults.…”
Section: Introductionmentioning
confidence: 99%
“…1 Newborns commonly experience pain due to a variety of reasons. 2,3 For example, in the first 3e4 days of life, they are subjected to routine invasive procedures such as vitamin K1 injections, 4 checking the anus for patency, 5 hepatitis B vaccination, 6 tuberculosis vaccination, 7 and neonatal screening tests. 8,9 Scientific evidence demonstrates that although newborns lack the ability to express their discomfort and stress in words, they tend to experience the pain at a higher intensity than older children and adults.…”
Section: Introductionmentioning
confidence: 99%
“…The exact amount of each solution was not measured in this study; however, it was likely approximately 0.1 mL based on the report of Mokhnach et al [5]. In many studies supporting the pain-relieving effects of sucrose or human milk, at least 0.2 mL to 2 mL of solution was administered [9,15,19,20]. In addition, a single dose of the solution was administered just once 2 minutes prior to the examination; thus, its effect may not have lasted long enough to span the 2~3 minutes of the examination.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that a minimum amount of 0.1 mL of 24% sucrose was effective in reducing pain in preterm and newborn infants undergoing a single heel lance [7,8]. In another recent study, 0.5 mL of 24% sucrose demonstrated better pain-relieving effects than 0.2 mL of the same solution in infants at a gestational age of 28 weeks and weight >1,000 g undergoing venipuncture [9]. However, these studies employed painful, tissue-damaging procedures that are quite short-lasting.…”
Section: Introductionmentioning
confidence: 99%
“…[26] It was showed that, neonates received better pain relief from 0.5 ml than 0.2 ml sucrose during venipuncture which support our results as we used the same dose. [27] 5. CONCLUSION…”
Section: Discussionmentioning
confidence: 99%